Livestock as an effective asset for sustainable poverty reduction: a case study of Sindh, Pakistan - S Hirashima,; Hideo Tominaga,; Yukio Ikeda, (Agricultural Economics Research Review, 2023)
In this paper, we have discussed essentially the following three issues. The first issue relates to the short-run nature of the on-going poverty reduction strategy. We have emphasized the importance of long-run approach to this issue. The second issue is on the importance of sustainability of improved income through policy intervention. We have focused on the role of livestock, in particular the river-type buffalo, as an effective rural asset for ensuring sustainability of the household income of small farmers. The third issue is on the workable and effective prescriptions for immediate policy action. The ‘Buffalo Calves Salvation Scheme’ is one of these.